EFFECT OF N-ACETYLCYSTEINE ON DERANGED RENAL FUNCTIONS IN PATIENT RECEIVING NON IONIC RADIO CONTRAST: Effect of N-Acetylcysteine - Kamal, Dr Mahjabeen Mehmood; ., Anila Faisal (Pakistan Armed Forces Medical Journal, 2013)
Objective: To determine the effect of N-Acetylcysteine (NAC) on deranged renal functions in patients receiving non-ionic contrast. Study Design: Quasi- experimental study. Place and Duration of Study: The study was conducted in the Department of Radiology, DHQ Hospital Rawalpindi, RMC and Allied hospitals from August 2011 to January 2012. Methodology: Eighty consecutive patients with deranged renal function tests (RFTs) (creatinine level ≥ 1.3 mg/dl and ≤ 3 mg/dl and urea level > 50 mg/dl) were included in this study. These patients were advised to take at-least eight sachets of NAC to talling to 1,600 mg (one sachets is 200 mg) within two days with good hydration (6 to 8 glasses of water) prior to Contrast Enhanced Computer Tomographic (CECT) scan. After completion of NAC recommended dose, the RFTs are repeated to confirm the controlled range. The patients are allowed for CECT, if the serum urea level ≤ 50 mg/dl (reference range 0-50mg/dl) and serum creatinine level ≤ 1.3 mg/dl (reference range 0.2-1.2 mg/dl). Results: The mean age of the patient is 53.98±15.4 years. The use of NAC extensively improves the serum urea level of 73 out of 80 patients (91.3%) with a significance of 0.0001 to a normal level (<50 mg/dl). Similarly, serum creatinine level of 71 out of 80 patients (88.8%) with a significance of 0.0001 has an improved from reference range (≤1. 2 mg/dl). Conclusion: Use of NAC resulted in improved serum urea and creatinine levels in the majority of patients.